2015
DOI: 10.4103/0971-3026.169445
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury and the post-concussion syndrome: A diffusion tensor tractography study

Abstract: Aim:The aim of the present study is to evaluate diffusion tensor tractography (DTT) as a tool for detecting diffuse axonal injury in patients of acute, mild, and moderate traumatic brain injury (TBI), using two diffusion variables: Fractional anisotropy (FA) and mean diffusivity (MD). The correlation of these indices with the severity of post-concussive symptoms was also assessed.Materials and Methods:Nineteen patients with acute, mild, or moderate TBI and twelve age- and sex-matched healthy controls were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…34 Although relationships between headache characteristics and cortical thickness were not specifically assessed, results did indicate that more post-traumatic symptoms (including headache) related to thinner cortex in a variety of frontal, temporal, and parietal areas in a cohort of male concussed hockey players. Similarily, D'Souza et al 36 found white matter changes in patients with mild to moderate head trauma using diffusion tensor imaging. Results showed a correlation between white matter integrity loss and postconcussion symptom severity using the Rivermead Postconcussion Symptom Questionnaire, which is a questionnaire that assesses a variety of self-reported symptoms including headache, mood, physical problems, and cognitive problems.…”
Section: Discussionmentioning
confidence: 61%
“…34 Although relationships between headache characteristics and cortical thickness were not specifically assessed, results did indicate that more post-traumatic symptoms (including headache) related to thinner cortex in a variety of frontal, temporal, and parietal areas in a cohort of male concussed hockey players. Similarily, D'Souza et al 36 found white matter changes in patients with mild to moderate head trauma using diffusion tensor imaging. Results showed a correlation between white matter integrity loss and postconcussion symptom severity using the Rivermead Postconcussion Symptom Questionnaire, which is a questionnaire that assesses a variety of self-reported symptoms including headache, mood, physical problems, and cognitive problems.…”
Section: Discussionmentioning
confidence: 61%
“…However, due to a shortage of scientific evidence supporting the use of the 6-hour LOC criterion to distinguish between concussion and DAI, and the low sensitivity of conventional brain MRI in the detection of DAI lesions, the accuracy of a DAI diagnosis is limited [4,11,12]. In addition, axonal injuries have been detected in many concussion cases with less than 6-hour LOC, and there are opposing opinions regarding the applicability of the term diffuse in DAI [7,11,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends are observed in DTI studies on mTBI. For instance, two additional studies (D'souza et al, ; Toth et al, ) report increased MD and decreased FA during the acute phase of mTBI as compared to age‐ and sex‐matched healthy controls with FA decreases persisting at 1 month (Toth et al, ). An additional TBSS study reports increased RD and decreased FA in the subacute phase of mTBI without post‐concussion syndrome as compared to healthy controls with FA decreases persisting at 6 months (Messé et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends are observed in DTI studies on mTBI. For instance, two additional studies (D'souza et al, 2015;Toth et al, 2013) report increased MD and decreased FA during the acute phase of mTBI as compared to age-and sex-matched healthy controls with FA decreases persisting at 1 month (Toth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%